Design Thinking in Software and AI Projects Proving Ideas Through Rapid Prototyping - Stackowiak, Robert; Kelly, Tracey; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2020)
Learn the fundamentals of Design Thinking and how to apply Design Thinking techniques in defining software development and AI solutions. Design Thinking is an approach to innovation which identifies problems and generates solution ideas that can be rapidly proven through prototyping. This book provides a brief history of Design Thinking and an overview of the process. It then drills down into more detail regarding methods and tools used in a Design Thinking workshops leading to useful prototypes. Guidance is provided on: Preparing for a Design Thinking Workshop Uncovering potential business problems that might be solved Prioritizing potential solutions Identifying and characterizing stakeholders Choosing the right prototypes for development Limiting scope and best practices in prototype building The book concludes with a discussion of best practices in operationalizing successful prototypes, and describes change management techniques critical for successful adoption. You can use the knowledge gained from reading this book to incorporate Design Thinking techniques in your software development and AI projects, and assure timely and successful delivery of solutions. You will: Gain foundational knowledge of what Design Thinking is and when to apply the technique Discover preparation and facilitation techniques used in workshops Know how ideas are generated and then validated through prototyping Understand implementation best practices, including change management considerations.
Chapter 1: Design Thinking Overview and History -- Chapter 2: Preparing for a Workshop -- Chapter 3: Problem Definition -- Chapter 4: Solution Definition -- Chapter 5: Prototype Creation -- Chapter 6: Production Development -- Chapter 7: Production Rollout -- Chapter 8. Appendix A: Sources.
Keywords: Management information systems; Software Management